Proceedings of the Second ACM International Conference on AI in Finance 2021
DOI: 10.1145/3490354.3494373
|View full text |Cite
|
Sign up to set email alerts
|

Multi-view contrastive self-supervised learning of accounting data representations for downstream audit tasks

Abstract: International audit standards require the direct assessment of a financial statement's underlying accounting transactions, referred to as journal entries. Recently, driven by the advances in artificial intelligence, deep learning inspired audit techniques have emerged in the field of auditing vast quantities of journal entry data. Nowadays, the majority of such methods rely on a set of specialized models, each trained for a particular audit task. At the same time, when conducting a financial statement audit, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Schreyer et al [8,9] constructed an autoencoder neural network to sample journal entries in their two papers. They fed attributes of these journal entries into the resulting autoencoder.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Schreyer et al [8,9] constructed an autoencoder neural network to sample journal entries in their two papers. They fed attributes of these journal entries into the resulting autoencoder.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nowadays, applied representation learning techniques encompass, autoencoder neural networks [53], adversarial autoencoders [51], or variational autoencoders [68]. Lately, self-supervised learning techniques have been proposed to learn rich representations for multiple downstream audit tasks [48]. Concluding the literature survey and, to the best of our knowledge, this work presents the first step towards learning accounting data representations in a confidentiality-preserving manner.…”
Section: Related Workmentioning
confidence: 99%
“…Split Learning: When investigating the representations learned by AENs [52] it becomes apparent that representations learned by early (later) layers of the encoder (decoder) function encode detailed attribute characteristics, e.g., a client's journal entry attribute co-occurrence pattern. In contrast, the later encoder (early decoder) function layers learn representations that encode general or 'meta' posting patterns, e.g., a client's prevalent financial accounting principles [47,48]. Derived from this observation and to increase the level of privacy, we apply principles of Split Learning (SL) [20].…”
Section: (B)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Nonnenmacher et al [32] and Schreyer et al [40] demonstrated that AENNs could be used to improve audit sampling during an audit process. Furthermore, it was shown that AENNs can be trained in a self-supervised learning setup to detect accounting anomalies and complete additional down-stream audit tasks [38].…”
Section: Detection Of Accounting Anomaliesmentioning
confidence: 99%